PEMBERDAYAAN KADER DALAM MELAKUKAN KONSELING GIZI DAN ANC PADA IBU HAMIL KEK UNTUK MENCEGAH STUNTING DI WILAYAH KERJA PUSKESMAS SRI KUNCORO KABUPATEN BENGKULU TENGAH TAHUN 2025 - Maigoda, Tonny; Rizal, Ahmad; Suryani, desri; Yunita , Yunita; Natan, Okdi; Mariati, Mariati (Poltekkes Kemenkes Bandung, 2025)
Chronic Energy Deficiency (CED) in pregnant women is a condition experienced by pregnant women due to an imbalance in energy and protein nutritional intake, resulting in inadequate intake of nutrients needed by the body. Inadequate nutritional intake in pregnant women not only endangers the mother's health but also impacts the delayed growth and development of the fetus. Adequate nutritional intake in pregnant women is seen from their nutritional status, which can be illustrated by the measurement of the mid-upper arm circumference (MUAC). The occurrence of CED in pregnant women carries the risk of abortion, bleeding, prolonged labor, infection, low birth weight (LBW), prematurity, birth defects, and indirect causes of maternal death. The objective is to improve the skills of cadres in Empowering Cadres in Providing Nutrition Counseling and ANC for Pregnant Women with CED to Prevent Stunting in the Work Area of ​​the Sri Kuncoro Community Health Center, Central Bengkulu Regency in 2025. The methods of this activity include lectures, discussions, Q&A with cadres, counseling, early detection practices, and training cadres in food processing to prevent CED in pregnant women. The results showed an increase in knowledge scores before and after training on cadres' knowledge and skills in providing nutrition counseling and ANC to pregnant women with special needs (KE), with a score from 78 to 83.6, with a minimum pre-test score of 68 and a maximum score of 76. Meanwhile, the post-test score increased from a minimum score of 84 to 92 after being provided with knowledge and skills in providing nutrition counseling and ANC to pregnant women with special needs (KE). In conclusion, this activity resulted in a significant impact on knowledge, counseling skills, changes in attitudes and behavior of cadres, and their impact on maternal health services in the Posyandu area.